Osteosarcoma and Ewing Sarcoma of Bone: An Italian Mono-Institutional Epidemiological Study - Cristina Ferrari; Giovanna Magagnoli; Roberta Laranga; Giuseppe Bianchi; Elisa Carretta; Marilena Cesari; Katia Scotlandi; Nicola Baldini; Davide Maria Donati; Marco Gambarotti (Diagnostics, 2025)
Background/Objectives: Musculoskeletal neoplasms are rare and challenging diseases. Their geographic pattern varies worldwide, and no studies analyze their distribution in Italy. The aim of this study was to investigate a possible association between clinical variables to a period of diagnosis and geographic origin in Italy. Moreover, we wanted to describe the survival rate of bone osteosarcoma (OS) and Ewing sarcoma (EwS) from the Rizzoli Orthopaedic Institute (IOR) experience. Methods: We retrospectively reviewed 3098 diagnoses of high-grade bone OS and EwS made at the IOR in the past 40 years (1982–2021). Incidence, measures of associations, and survival rates have been analyzed. Results: The time of diagnosis and geographic origin were associated either with each other or with age and stage of tumor. Overall, the 10-year survival rate was 54% (95% CI 52–56) and 53% (95% CI 50–56) for bone OS and EwS, respectively. Multivariate analyses showed that adverse factors at diagnosis are age, location, stage, and time of diagnosis, in both cohorts. Conclusions: We confirmed known prognostic factors, and owing to the large cohort, we highlight their importance in clinical practice. No differences were observed in patient survival associated with different areas of Italy, although geographic origin was associated with most clinical variables analyzed, suggesting a further factor to investigate. Given the above-mentioned results, a Sarcoma Specialist Network with a recognized expertise is determinably in charge of the management of sarcomas.